2017
DOI: 10.1513/annalsats.201606-481fr
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis in the African Diaspora

Abstract: Identifying mutations that cause cystic fibrosis (CF) is important for making an early, unambiguous diagnosis, which in turn is linked to better health and a greater life expectancy. In patients of African descent, a molecular diagnosis is often confounded by the fact that the majority of investigations undertaken to identify causative mutations have been conducted on European populations, and CF-causing mutations tend to be population specific. We undertook a survey of published data with the aim of identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…It is important to mention that of the five patients with the variants identified in this study, three have African ancestry, one has Latin European ancestry and one is unaware of the origin of the grandparents. In addition, the three mutations, G85E, A559T and R117H, in heterozygosis with the rearrangements found in this work, are part of the African Diaspora as observed in the study by Stewart and Pepper ().…”
Section: Discussionsupporting
confidence: 76%
“…It is important to mention that of the five patients with the variants identified in this study, three have African ancestry, one has Latin European ancestry and one is unaware of the origin of the grandparents. In addition, the three mutations, G85E, A559T and R117H, in heterozygosis with the rearrangements found in this work, are part of the African Diaspora as observed in the study by Stewart and Pepper ().…”
Section: Discussionsupporting
confidence: 76%
“…This is key given that implicit bias linking CF to Caucasians only may lead to delayed diagnosis, and continued attention should be paid to early genetic diagnosis in this group. 27 However, our data also demonstrate that malnutrition and stunting remain a concern, with 12% of infants falling below a z-score of −2 for both weight and height at the end of the time period studied. The BONUS study also found stunting in a smaller cohort of newborn screened infants.…”
Section: Discussionmentioning
confidence: 48%
“…Weight outcomes appear to be improving significantly for black infants. This is key given that implicit bias linking CF to Caucasians only may lead to delayed diagnosis, and continued attention should be paid to early genetic diagnosis in this group …”
Section: Discussionmentioning
confidence: 99%
“…6 Even among investigations of Latino populations, there have been limited efforts to describe the genetic profile of CF in the Caribbean. 7 There is considerable genetic heterogeneity between Latino populations and within the Caribbean. 8 In this study, full genetic sequencing of CFTR was done in Dominican and Puerto Rican patients with CF to describe the spectrum of CFTR variants.…”
Section: Discussionmentioning
confidence: 99%
“…CFTR variants are population‐specific and the spectrum of known CFTR variants is based largely on investigations of White populations . Even among investigations of Latino populations, there have been limited efforts to describe the genetic profile of CF in the Caribbean . There is considerable genetic heterogeneity between Latino populations and within the Caribbean …”
Section: Introductionmentioning
confidence: 99%